The good jobs strategy : how the smartest companies invest in employees to lower costs and boost profits - Ton, Zeynep (Boston : New Harvest, Houghton Mifflin Harcourt, 2014)
" For decades, jobs with good pay and decent benefits in service, manufacturing, and retail have gone overseas, eviscerating America's middle class and setting off a chain reaction of problems for the country as a whole. Up until now, defenders of the new system have argued that American corporations, to stay competitive internationally, must cut wages and benefits and essentially squeeze as much value as possible out of each worker. But this is backward: workers aren't a cost. They are a company's greatest asset. Ton argues that good jobs and happy, well-compensated employees are in fact a key element of a virtuous cycle for companies that results in low prices and increased profitability. The author's work focuses on retailing, where bad jobs would seem to be most embedded in the fabric of the business; but she also reveals how her insights and conclusions can be applied successfully in most service businesses"--
An unnecessary sacrifice -- Great operations need great people -- The penalties of going cheap on retail labor -- Model retailers : who knew it could be this good? -- Offer less -- Standardize and empower -- Cross-train -- Operate with slack -- Seizing strategic opportunities -- Values and constraints.
Includes bibliographical references and index.
Keywords: Job creation -- United States; Manpower policy -- United States; Quality of work life -- United States